1990
DOI: 10.1177/0734242x9000800136
|View full text |Cite
|
Sign up to set email alerts
|

Emissions of Organic Micropollutants From Discontinuously Operated Municipal Waste Incinerators

Abstract: The emission of particles and organic micropollutants (PAH, PCDD and PCDF) was measured from three intermittently operated municipal waste incinerators of medium size. The mutagenicity of the stack gas samples were measured as well. The results show a good agreement between the PAH emitted and the mutagenicity in the stack gases, but none of these parameters correlate with the PCDD/PCDF content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Approximately 88% of the facilities (seven out of eight) demonstrated that the PCDD/F emissions were approximately 2.3-2727 times higher under start-up conditions than under normal conditions [30][31][32][33][34]37,39]. As for the PCDD/F emissions under shut-down conditions, one of the two facilities reported approximately 5.5-212 times higher emissions [30], while the other reported approximately 5%-50% lower emissions compared to normal operating conditions [35]. The increase in PCDD/F emissions during start-up and shut-down is likely due to incomplete combustion during these conditions [31][32][33]38,40].…”
Section: Waste Incinerationmentioning
confidence: 99%
See 4 more Smart Citations
“…Approximately 88% of the facilities (seven out of eight) demonstrated that the PCDD/F emissions were approximately 2.3-2727 times higher under start-up conditions than under normal conditions [30][31][32][33][34]37,39]. As for the PCDD/F emissions under shut-down conditions, one of the two facilities reported approximately 5.5-212 times higher emissions [30], while the other reported approximately 5%-50% lower emissions compared to normal operating conditions [35]. The increase in PCDD/F emissions during start-up and shut-down is likely due to incomplete combustion during these conditions [31][32][33]38,40].…”
Section: Waste Incinerationmentioning
confidence: 99%
“…[35,36,39] Eight facilities assessed the emission of polychlorinated dibenzodioxins and polychlorinated dibenzofurans (PCDD/Fs) under start-up and normal operating conditions [30][31][32][33][34][35]37,39]. Two of these also assessed the PCDD/F emissions under shut-down conditions [30,35]. Approximately 88% of the facilities (seven out of eight) demonstrated that the PCDD/F emissions were approximately 2.3-2727 times higher under start-up conditions than under normal conditions [30][31][32][33][34]37,39].…”
Section: Waste Incinerationmentioning
confidence: 99%
See 3 more Smart Citations